Periodontal disease and its connection to systemic biomarkers of cardiovascular disease in young American Indian/Alaskan natives. Issue 2 (23rd February 2018) - Delange, Nicole; Lindsay, Suzanne; Lemus, Hector; Finlayson, Tracy L.; Kelley, Scott T.; Gottlieb, Roberta A.
Abstract: Background: Periodontal disease has been shown to be associated with cardiovascular disease (CVD). No known studies evaluate the relationship between periodontal disease status and biomarkers of CVD risk in the American Indian/Alaskan Native (AI/AN) population despite their disproportionately high rates of poor oral health and cardiovascular disease–related outcomes. This study compared levels of interleukin (IL)‐6 and C‐reactive protein (CRP) across increasing severity of periodontal disease status among younger adults between the ages of 21 and 43 years. Methods: Plasma levels of IL‐6 and CRP were measured in adult participants (ages 21 to 43 years) as part of a study of periodontal disease and CVD risk among an AI/AN population in southern California (n = 59). Periodontal evaluations were performed and disease status was classified into three categories based on highest probing depth (none/mild: < 3 mm; moderate: 4 to 5 mm; severe: ≥6 mm). Participants with known systemic disease or active infection were excluded. Results: Severe periodontitis was significantly associated with increased levels of IL‐6 compared with those with none or mild periodontitis before controlling for other variables ( P  = 0.02), but lacked significance after controlling for sex, BMI, smoking status, and high‐density lipoprotein ( P  = 0.09). Moderate periodontal disease was positively associated with IL‐6 levels after controlling for potential confounders ( P  = 0.01). Periodontal status was not associated with CRP, before or after adjusting for covariates. Conclusions: In this otherwise healthy AI/AN adult sample, moderate periodontal disease compared with none or mild periodontal disease was associated with increased levels of IL‐6. High levels of CRP found in this population warrant further research.